ASPEN HYSYS SIMULATION AND COMPARISON BETWEEN ORGANIC SOLVENTS (SULFOLANE AND DMSO) USED FOR BENZENE EXTRACTION - Zaiz, T; Lanez, H; Kechida, B (جامعة الوادي - university of el oued, 2013)
Due to the high increase of the production of aromatic hydrocarbons: benzene, toluene and xylenes BTX from oil because of the large activity of their big markets especially with the availability of great quantities of these aromatic fractions in the oil. This study has two main parts the first presents a general vision of the aromatic hydrocarbons, the second is going to focus on the liquidliquid extraction with the selected solvents as a separation method. The solvent selection depends on many properties. In this second part there will be a simulation (conception and execution) of the liquid-liquid extraction of aromatics by two different organic solvents Sulfolane and DMSO followed by a comparison between the results obtained by the simulation. The simulator used will be ASPEN HYSYS 7.2. The results of the simulation showed that the use DMSO is better than Sulfolane because of the separation efficiency the economic value and the regeneration rate although its use is more dangerous (more toxic) than the Sulfolane
Article
Keywords: Extraction, Aromatic, DMSO, Sulfolane, Simulation, HYSYS.